Canine salivary gland carcinoma treated with stereotactic body radiation therapy: a retrospective case series - Gualtieri, Patricia; Martin, Tiffany; Leary, Del; Lana, Susan E.; LaRue, Susan M.; Boss, Mary-Keara (Frontiers in Veterinary Science, 2023)
Objective: The aim of this study was to describe therapeutic outcome of dogs with locally advanced salivary gland carcinomas (SGC) following stereotactic body radiation therapy (SBRT). Methods: A single institution retrospective study was conducted of client-owned dogs with macroscopic SGC treated with SBRT. Patient signalment, clinical characteristics, and treatment parameters were recorded. Clinical benefit was determined based on follow up physical examination and medical history. Progression-free interval (PFI), median survival time (MST), and disease-specific survival (DSS) were calculated using Kaplan–Meier analysis. Acute and late toxicity were recorded according to VRTOG criteria. Results: Six patients were included in the study. Tumor origins were mandibular (n=3), parotid (n=2) and zygomatic (n=1) salivary glands. The SBRT prescription was 10 Gy x 3 daily or every other day. All patients (100%) experienced clinical benefit from treatment at a median time of 34 days (range 28-214). No local or regional nodal failure was reported following SBRT. Progressive pulmonary metastatic disease was documented in three dogs (50%). The median PFI was 260 days (range 43-1014) and the MST was 397 days (range 185-1014). Median DSS was 636 days (range 185-1014). Four dogs (66.6%) died of confirmed or suspected metastatic SGC. Reported acute side effects included grade 2 mucositis (n=1) and vision loss (n=1). No late side effects were recorded. Conclusion: This study suggests that SBRT may provide durable local control for invasive SGC in dogs. Further investigation in a larger cohort of patients is warranted. The incidence of reported acute and late toxicity was low.